Preparation and application of biomass-based porous carbon with S, N, Zn, and Fe heteroatoms loading for use in supercapacitors. (January 2022) - Wang, Jingyue; Xu, Yuelong; Yan, Meifang; Ren, Bin; Dong, Xiaoxi; Miao, Junfeng; Zhang, Lihui; Zhao, Xinqiang; Liu, Zhenfa
Abstract: Porous biomass-carbon materials for supercapacitor applications have recently attracted attention. Chitin, which has abundant amides and hydroxyl groups, was used as an ideal precursor for carbon in this work. The chitin was treated with a one-step method to produce a heteroatom-loaded porous carbon material, and its electrochemical properties were significantly improved through the introduction of loaded elements. A mixture of chitin, zinc chloride, and heteroatoms was carbonized to obtain heteroatoms (N and S) and the bimetallic sulfide loaded hierarchical porous carbon. Then, the porous carbon with S, N, Zn, and Fe heteroatoms loading was used to prepare a supercapacitor with a specific capacitance of 277.4 F g −1 at 1 A g −1 . In addition, the supercapacitor had a specific capacitance retention rate of 90% at 5 A g −1 after 10, 000 cycles. Therefore, hierarchical porous carbon materials loaded with heteroatoms and bimetallic sulfide were prepared by carbonization activation with chitin as the precursor. The resulting supercapacitor showed that the as-prepared porous biomass materials possessed ideal charging-discharging performance. Moreover, this work provides strategies for obtaining metal sulfides and heteroatom co-loading of carbon materials with excellent properties using a simple and efficient one-step method for renewable energy storage device applications. Highlights: Porous carbon doped with nitrogen, iron, zinc and sulfur is rationally obtained from biomass chitin through one-step preparation/activated method. Porous carbon exhibits a large specific surface area and a specific capacitance. New finding in excellent electrical properties of the novel design is revealed. Porous carbon are assembled into super capacitors to light LEDs.